PERBEDAAN GAYA KEPEMIMPINAN DALAM PERSPEKTIF MASKULIN dan FEMININ - Ryani Dhyan Parashakti (Universitas Mercu Buana, 2015)
At the present time there are enough women who are leaders and can work well in performing their duties and functions. There are at least five (5) requirements that have been met in order to achieve effective leadership are: (1) knowledge within the organization, (2) has a good reputation and school reports, (3) have the ability and strategic skills, (4) has a personality and high integrity, and (5) have high motivation power. Although sex differences that men and women are biologically, but in reality, gender is considered normal treatment is expected to be feminine women and men are expected to be masculine. Basically women and men having sex-role stereotypes that will affect their personality and behavior. The purpose of writing this article is to see whether the manager's leadership style differs from the male leadership styles of women managers and managers discuss how men and women describe their leadership style tendencies. This article discusses the characteristics of femininity and masculinity of some experts, transformational vs. transactional leadership style, as well as views of male managers and female managers on their leadership style. Keywords : Leadership style, feminine vs. masculine, transformational vs. transactional leadership style